2015
DOI: 10.5860/crl.76.1.43
|View full text |Cite
|
Sign up to set email alerts
|

“Pretty Rad”: Explorations in User Satisfaction with a Discovery Layer at Ryerson University

Abstract: Web-scale discovery systems are becoming prevalent in research libraries. Although a number of studies have explored various impacts of discovery systems, few studies exist on user satisfaction. The investigators of this study evaluated user satisfaction with the discovery service Summon at Ryerson University, using online questionnaires and in-person focus groups. Results indicated a high level of satisfaction overall, although this was heavily influenced by the quality of search results over ease of use. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…In one instance, using online questionnaires and in-person focus groups, researchers found users had a high level of satisfaction with their institution's discovery environment, largely attributed to the quality of search results over ease of use. 16 Hamlett and Georgas (2019) conducted a mixed-methods user experience study to understand student perceptions of relevancy in Primo. This study found that participants believed Primo to return relevant results (with an average score of 8.3 out of 10).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In one instance, using online questionnaires and in-person focus groups, researchers found users had a high level of satisfaction with their institution's discovery environment, largely attributed to the quality of search results over ease of use. 16 Hamlett and Georgas (2019) conducted a mixed-methods user experience study to understand student perceptions of relevancy in Primo. This study found that participants believed Primo to return relevant results (with an average score of 8.3 out of 10).…”
Section: Literature Reviewmentioning
confidence: 99%
“…At Illinois State University, they found that most students were able to easily locate needed materials using EBSCO's Web-scale discovery layer, although the authors also cautioned that users will continue to need to access some databases directly as discovery layers cannot fill all the gaps and functionality needed by academic faculty (Williams and Foster 2011). The need to access specific databases for more advanced searching as compared to the broad services of a Web-scale discovery layer was supported in a study at Ryerson University in Toronto where it was found that students, both graduate and undergraduate, are most likely to use the resources their instructors recommend (Lundrigan, Manuel, and Yan 2015). This issue reinforces the need for libraries to market their resources and work with faculty to demonstrate how the library's discovery layer can meet their needs if the library wants to see increased usage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While ideally Primo should make searching for library resources more efficient, user friendly, and accessible for a broader range of users, caution should be used, especially when considering more advanced users (Jarrett 2012). In summary, Primo and other Web-scale discovery layers may best match the needs of undergraduates and basic researchers, but do not meet the needs of graduate students and faculty (Lundrigan, Manuel, and Yan 2015;Nichols et al 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Lundrigan, Manuel, and Yan found that the majority of respondents to their user satisfaction survey were "very" or "moderately" satisfied with the Summon discovery layer, though this was less true for graduate students and students in certain disciplines. 12 Student participants in Asher, Duke, and Wilson's study indicated a preference for discovery tools and Google Scholar over traditional library tools such as the catalog and databases. 13 As Gross and Sheridan conclude, "there is no doubt that the students found [the webscale discovery tool] an easy way to get results and probably easier than the various options they were previously faced with."…”
Section: Literature Reviewmentioning
confidence: 99%